SAFETY PRACTICES FRAMEWORK FOR CONSTRUCTION PROJECT OF UNDERGROUND KVMRT STATION - AHMAD TAJUDDIN, IFFAH NADHIRAH (Universiti Teknologi PETRONAS, 2020)
“Safety First” sign is commonly found almost everywhere to give an awareness to the society, especially at the area with potential to offer risk. This sign is an alarm for many ignorance people. Statistics and data reported from various agencies and sources such as Department of Safety and Health (DOSH) have shown that the number of occupational accidents including fatality and disability from the construction sector keep leading over other sectors in Malaysia since the past few years. This is due to the nature of work with an exposure of too many high-risk condition and hazardous environment which commonly involve hit from falling objects, confine spaces, fall from height and lifting activities. However, the safety implementation of the overall construction site also important to examine of how obedient and serious the stakeholders take into consideration. As the result of an increasing the accidents, it contributes a high percentage effect to our economic growth. In line with the efforts to reduce the occupational accidents at the construction site especially in Malaysia, this study purposely conducted to investigate on the safety implementation and management throughout the construction stages.